2012
DOI: 10.1111/j.1469-0691.2011.03594.x
|View full text |Cite
|
Sign up to set email alerts
|

Two weeks of postsurgical therapy may be enough for high-risk cases of endocarditis caused by Streptococcus viridans or Streptococcus bovis

Abstract: The duration of antimicrobial therapy after surgery for infective endocarditis (IE) is controversial. A short course of postsurgical therapy is currently accepted only for patients with negative valve culture. We performed a retrospective (1994-2008) analysis of patients who underwent surgery for IE in our hospital and had a high risk of complications ( one of more of the following: <2 weeks of antibiotic treatment before surgery; embolism; perivalvular extension; and positive valve culture) to compare outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…If the resected tissue is culture negative, then it may be reasonable for the duration of postoperative treatment given less the number of days of treatment administered for native valve infection before valve replacement. This, however, has been challenged by retrospectively collected data from 2 different medical centers 116,117 that suggest that 2 weeks of antibiotic therapy may be sufficient in patients who undergo valve surgery and have negative valve tissue cultures, particularly in IE cases caused by VGS or Streptococcus gallolyticus (bovis). Whether a 2-week treatment course would be sufficient after valve surgery in patients with positive valve cultures either was not addressed in 1 survey 116 or included only 5 patients in the other.…”
Section: Antimicrobial Treatment Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…If the resected tissue is culture negative, then it may be reasonable for the duration of postoperative treatment given less the number of days of treatment administered for native valve infection before valve replacement. This, however, has been challenged by retrospectively collected data from 2 different medical centers 116,117 that suggest that 2 weeks of antibiotic therapy may be sufficient in patients who undergo valve surgery and have negative valve tissue cultures, particularly in IE cases caused by VGS or Streptococcus gallolyticus (bovis). Whether a 2-week treatment course would be sufficient after valve surgery in patients with positive valve cultures either was not addressed in 1 survey 116 or included only 5 patients in the other.…”
Section: Antimicrobial Treatment Perspectivesmentioning
confidence: 99%
“…Whether a 2-week treatment course would be sufficient after valve surgery in patients with positive valve cultures either was not addressed in 1 survey 116 or included only 5 patients in the other. 117 Histopathological evidence of bacteria with valve tissue Gram staining in patients with negative tissue cultures can represent killed organisms and is not a factor in defining the length of therapy after valve surgery. 110 For patients with NVE who undergo valve resection with prosthetic valve replacement or repair with an annuloplasty ring, there is a lack of consensus as to whether the postoperative treatment regimen should be one that is recommended for prosthetic valve treatment rather than one that is recommended by guest on http://circ.ahajournals.org/ Downloaded from for native valve treatment.…”
Section: Antimicrobial Treatment Perspectivesmentioning
confidence: 99%
“…The saving in patient complications and hospital stay on account of short-course treatment has already been a common goal of various IE studies. [26,27]. The potential protective effect of shorter courses of beta-lactams, ranging from lower rates of antibiotic-related toxicity to the risk of suffering from C. difficile infections or for the selection of vancomycin-resistant E. faecium [28][29][30].…”
Section: Plos Onementioning
confidence: 99%
“…The authors observed that a 2 week post-surgical course of AT was not associated with higher relapse rates if valve culture results were negative. 52 More recently, a Spanish retrospective study carried out by Muñoz et al 53 found that short-course (median 15 days) post-operative AT has a similar effectiveness to longer-course (median 32 days) treatment for patients who underwent surgery for IE and had a high risk of complications (short course of AT before surgery, embolic events, extension of infection beyond the valve and positive valve culture). Moreover, on multivariate analysis, IE due to Streptococcus viridans or Streptococcus bovis was independently associated with short-course AT.…”
Section: Iementioning
confidence: 99%
“…Moreover, on multivariate analysis, IE due to Streptococcus viridans or Streptococcus bovis was independently associated with short-course AT. 53…”
Section: Iementioning
confidence: 99%